Predominance of metallo-beta-lactamase blaVIM Genes in Clinical Isolates from Health Facilities in Nigeria: Role in Multidrug Resistance Surge - Etang UE; Moses AE; Akpan SS; Eyo AO; Moses EA (Ibom Medical Journal)
Background: The predominance of metallo-beta-lactamase (MBL) genes in Gram-negative bacteria (GNB) has been reported to contribute immensely in the emergence of multi-drug resistance (MDR) strains in hospital environments worldwide.